Host Ranges of the IncN Group Plasmid pCU1 and Its Minireplicon in Gram-Negative Purple Bacteria - Krishnan, B. Rajendra (1988)
The bacterial host ranges of the conjugatively self-transmissible IncN group plasmid pCU1 and its mobilizable miniderivative, pCU785, were examined. Species of the gram-negative purple bacteria were chosen for this study. Conjugative mobilization of pCU785 into a wide variety of bacteria was facilitated by the presence of oriT of the broad-host-range plasmid RK2 in pCU785. Although the host range of the IncN tra system of pCU1 is broad, the host range of its replicon is limited. However, the pCU1 replicon can be maintained in Agrobacterium, Bradyrhizobium, and Rhizobium species under conditions that select for plasmid maintenance. It is lost efficiently from these populations on release of selection.